2015
DOI: 10.1111/jphp.12330
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram-loaded immediate and extended release vaginal tablets for the localised treatment of cervical cancer

Abstract: Objectives To develop and manufacture both immediate and sustained release vaginal tablets containing the anticancer drug disulfiram, which has the potential to be used as a non‐invasive treatment for cervical cancer. Methods Disulfiram‐loaded vaginal tablets were manufactured at pilot scale using the direct compression method. These tablets were tested in accordance with the European Pharmacopeia testing of solid dosage form guidelines. They were also tested using a biorelevant dissolution method as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Previous studies developed a vaginal tablet of DS to be used in HeLa and Ca-Ski cells for the localised treatment of cervical cancer [28,42]. This study showed animal experiments provided a basis for systemic application of DS.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies developed a vaginal tablet of DS to be used in HeLa and Ca-Ski cells for the localised treatment of cervical cancer [28,42]. This study showed animal experiments provided a basis for systemic application of DS.…”
Section: Discussionmentioning
confidence: 80%
“…Baffoe et al describe the manufacture and testing of both immediate and sustained release vaginal tablets containing 130 mg of the drug disulfiram [ 73 ]. Disulfiram has been used safely in the clinic for many years to treat alcoholism and has shown potential anti-tumour activity as it can induce apoptosis in some cell lines and reduce cell growth in certain tumours [ 74 ].…”
Section: Localised Delivery Of Chemotherapeutic Drugsmentioning
confidence: 99%
“…Baffoe et al demonstrate that disufiram has a dose-dependent inhibition of the HeLa cervical cancer cell line with an IC 50 value of 124.3 nM, which is significantly more therapeutic than cisplatin with an IC 50 value of 2.2 μM against the same cell line. Furthermore, they show, using a bio-relevant dissolution model, that their immediate and sustained release tablets can release disulfiram at 25,000 to 35,000 times its IC 50 concentration [ 73 ]. A multicentre observational study in 256 patients with histologically proven CIN I demonstrated a 75.5% regression rate (the CIN was completely eradicated) to a negative histology after twice-weekly administration of bovine-colostrum containing vaginal tablets (Ginedie®) for 6 months [ 84 ].…”
Section: Localised Delivery Of Chemotherapeutic Drugsmentioning
confidence: 99%
“…Disulfiram (DSF), a drug currently used in the treatment of chronic alcoholism, has been shown to possess anti-tumor activity [21]. DSF can induce apoptosis in some cell lines and reduce cell growth in certain tumours including prostate cancer, breast cancer, lung cancer, leukaemia and cervical adenocarcinoma [21][22][23]. Furthermore, its chemical structure has a high affinity towards copper, which is essential for the tumour angiogenesis processes, and contributes to making DSF selective to cancerous cells, thus sparing healthy cells [24].…”
Section: Introductionmentioning
confidence: 99%